Uterine Fibroid Causing Acute Abdomen Due to Ischemic Gangrene: A Case Report - Isam Mohamed Babbiker; Ali Elimam; Isameldin Elamin Medani; Abdalmuein Ibrahim Omar (Archives of Case Reports, 2025)
Our case report discusses the importance of a rare presentation (twisted fibroid) causing severe abdominal pain and the diagnostic dilemma, which may result in ischemic gangrene, increasing morbidity and mortality. Again, it highlights the correlation between clinical picture and radiological findings, the important technical points when doing ultrasound for pelvic mass and its impact on management plan. The collaboration between the gynecologist and radiologist, along with timely intervention, leads to better outcomes.